2016
DOI: 10.1111/jeb.12982
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of dark colour in toucans (Ramphastidae): a case of molecular adaptation?

Abstract: In the last decades, researchers have been able to determine the molecular basis of some phenotypes, to test for evidence of natural selection upon them, and to demonstrate that the same genes or genetic pathways can be associated with convergent traits. Colour traits are often subject to natural selection because even small changes in these traits can have a large effect on fitness via camouflage, sexual selection or other mechanisms. The melanocortin-1 receptor locus (MC1R) is frequently associated with intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…While it is likely that mtDNA introgression and preservation can be explained by demography [ 29 ], it is plausible that brown hare could also obtain locally adapted alleles from the resident mountain hares, which are expected to represent only a tiny fraction of the total genome. A limitation of transcriptome studies is that they provide expression data and transcript genotypes only from the sampled tissue, such as kidney or liver, and might not be able to capture genes influencing traits such as coat color variation [ 55 , 56 ], muscle metabolism [ 57 ], diet specialization [ 58 ] and immunity [ 59 ]. At present, comprehensive surveys of this type of adaptive variation in species with unknown genomes are generally not possible.…”
Section: Discussionmentioning
confidence: 99%
“…While it is likely that mtDNA introgression and preservation can be explained by demography [ 29 ], it is plausible that brown hare could also obtain locally adapted alleles from the resident mountain hares, which are expected to represent only a tiny fraction of the total genome. A limitation of transcriptome studies is that they provide expression data and transcript genotypes only from the sampled tissue, such as kidney or liver, and might not be able to capture genes influencing traits such as coat color variation [ 55 , 56 ], muscle metabolism [ 57 ], diet specialization [ 58 ] and immunity [ 59 ]. At present, comprehensive surveys of this type of adaptive variation in species with unknown genomes are generally not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Although the eumelanin/dark phenotype is generally considered ancestral, and several past studies have found significant amino acid changes associated with organisms presenting a pheomelanin phenotype (Valverde et al, 1995;Theron et al, 2001;Mundy & Kelly, 2003;Nasti & Timares, 2015), some studies have found significant amino acid substitutions associated with darker phenotypes too. In a study on toucans (family: Ramphastidae), Corso et al, (2016) (Nachman et al, 2003;Nunes et al, 2011;Janssen & Mundy, 2013), instead of just one or two which is seen with lighter phenotypes (Rana et al, 1999;Theron et al, 2001;Mundy & Kelly, 2003;Rosenblum et al, 2004;. It could be that the maintenance or evolution of a darker phenotype requires or allows more nonsynonymous mutations, which is what we found with the darker pottos.…”
Section: Discussionsupporting
confidence: 49%
“…It could be that the maintenance or evolution of a darker phenotype requires or allows more nonsynonymous mutations, which is what we found with the darker pottos. Another interesting finding, which correlates with the many Mc1r variation studies on bird plumage, is that the more monochromatic taxon of interest (pottos) had more Mc1r amino acid changes than the more patterned taxon (Lorisinae) (Theron et al, 2001;Mundy, 2005;Pointer & Mundy, 2011;Bourgeois et al, 2012;Corso et al, 2016). Such a finding suggests that other pigment inducing genes may be responsible for the striking coat variations found in Lorisinae.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations